DEVELOPMENT OF EARLY WARNING SYSTEM FOR 3-PHASE ELECTRIC MOTOR MALFUNCTION DETECTION BASED ON LORA - Abdul Muis Mappalotteng; Muhammad Yusuf Mappeasse; Muhammad Irfan; Dewi Triantini (Jurnal Media Elektrik, 2024)
This study aimed to develop an early warning system for detecting malfunctions in three-phase electric motors using a LoRa-based microcontroller. Three-phase electric motors are vital components in industry, and their failure can cause significant downtime and financial losses. This system was designed to improve operational reliability and efficiency through remote monitoring and early detection of potential failures. Various sensors, including current, voltage, temperature, and RPM sensors, was installed on the motor to monitor its operational conditions. The collected data was sent via the LoRa network to the processing unit for further analysis and early warning. The study used Research and Development (R&D) approach with a prototyping development model, which included gathering requirements, designing, prototyping, and evaluating the system. Each stage was designed to ensure that the developed system can meet the expected operational and functional needs. It is expected that this system can prevent greater damage, reduce maintenance costs, and increase overall industrial productivity.